Kajian program pelayanan kesehatan jiwa puskesmas di Kabupaten Bolaang Mongondow - Kambey, Christ Eden; Palandeng, Henry M. F.; Kuhon, Frelly V. (UNIVERSITAS SAM RATULANGI, 2019)
Aims: To obtain a study of the suitability of the mental health care programs in primary health care in Bolaang Mongondow Regency according to existing instruments and regulations. Methods: The design used in this study is cross-sectional to measure the suitability of the mental health care programs in primary health care with the Domain 3 of World Health Organization-Assessment Instrument for Mental Health Systems (WHO-AIMS) 2.2 about Mental Health in Primary Health Care. The sample of this study are primary health cares in Poigar, Inobonto, Lolak, Mopuya, Doloduo, and Imandi which met the inclusion and not the exclusion criteria. Results: Physician-based primary health care are good in the aspects of new graduate training, assessment, protocol handling, referrals to expert doctors, interactions with mental health services, and prescribing medicines. Non-doctor primary mental health services is already good on the training aspects of new nurses’ graduates. Retraining for new health workers was followed by Poigar, Inobonto, and Imandi primary health care. Medicines for mental disorders are available at the Doloduo primary health care on their own initiative. Mental health counseling has not been carried out optimally by all observed primary health care. Conclusion: Primary health care’s mental health care programs in Bolaang Mongondow Regency has been endeavored to comply with existing instruments and regulations, in which at the time of this research, it was still not optimally implemented. Suggestions for all elements include the compilation of a clear breakdown of program costs, provision of drugs, training in early detection and management of mental disorders that are carried out on their own, as well as counseling that is carried out consistently.Keywords: mental healthcare programs, primary healthcare, Bolaang Mongondow Regency